A Leaky‐Integrate‐and‐Fire Neuron Analog Realized with a Mott Insulator. (30th January 2017) - Stoliar, Pablo; Tranchant, Julien; Corraze, Benoit; Janod, Etienne; Besland, Marie‐Paule; Tesler, Federico; Rozenberg, Marcelo; Cario, Laurent
Abstract : During the last half century, the tremendous development of computers based on von Neumann architecture has led to the revolution of the information technology. However, von Neumann computers are outperformed by the mammal brain in numerous data‐processing applications such as pattern recognition and data mining. Neuromorphic engineering aims to mimic brain‐like behavior through the implementation of artificial neural networks based on the combination of a large number of artificial neurons massively interconnected by an even larger number of artificial synapses. In order to effectively implement artificial neural networks directly in hardware, it is mandatory to develop artificial neurons and synapses. A promising advance has been made in recent years with the introduction of the components called memristors that might implement synaptic functions. In contrast, the advances in artificial neurons have consisted in the implementation of silicon‐based circuits. However, so far, a single‐component artificial neuron that will bring an improvement comparable to what memristors have brought to synapses is still missing. Here, a simple two‐terminal device is introduced, which can implement the basic functions leaky integrate and fire of spiking neurons. Remarkably, it has been found that it is realized by the behavior of strongly correlated narrow‐gap Mott insulators subject to electric pulsing. Abstract : The mammal brain is based on a network of closely connected neurons and synapses . The implementation of artificial neural networks directly in hardware requires therefore to develop artificial neurons and synapses that can be integrated in high‐density chips. Here, a two‐terminal device made of narrow‐gap strongly correlated Mott insulators is demonstrated, which implements the processing functions of the leaky‐integrate‐and‐fire artificial neuron.